Description of two new species of Noctuidae from China (Lepidoptera, Noctuoidea) - Saldaitis, Aidas; Benedek, Balázs; Visinskiene, Giedre (Zootaxa, 2011)
Two new Noctuidae species Orthosia wangwene and Cirrhia spalvota from China’s Sichuan province are described. Superficially the new species Orthosia wangwene and Cirrhia spalvota resemble related congeners but they can be distinguished by differences in wing pattern, genitalia and distribution. Checklists of China’s Orthosia and Eurasian Cirrhia are presented.